Obesity indicators and insulin resistance: a systematic review - Santos, Hully Cantão dos (2021)
The aim of this study was to verify the obesity indicators associated with insulin resistance by a systematic review. Two independent reviewers performed a search on Medline, Pubmed, LILACS, IBECS-ES and MedCarib databases up to April 2019, which included case-control, cohort or cross-sectional studies in adults. Articles’ quality was assessed by Newcastle-Ottawa Scale. PRISMA guideline for conducting the review were adopted, with protocol registered at PROSPERO. Twelve articles were included in the review. All studies reported a positive association between obesity indicators and HOMA-IR. Obesity indicator most positively associated with HOMA-IR was BMI, followed by waist circumference. Obesity indicators are associated with HOMA-IR and may be a useful tool for screening insulin resistance.